2022
DOI: 10.3389/fimmu.2022.816037
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Culture in Collagen Gel System

Abstract: Neutrophils (Neu) migrate rapidly to damaged tissue and play critical roles in host defense and tissue homeostasis, including the intestinal epithelia injuries and immune responses. Although their important roles in these diseases, they are challenging to study due to their short life span and the inability to cryopreserve or expand them in vitro. Moreover, the standard cell culturing on plastic plates (two-dimensional (2D) cultures) does not represent the actual microenvironment where cells reside in tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, the relationship between the heat shock response, intestinal barrier function, and gut microbiota nevertheless merits further investigation—particularly in terms of HA and HS. It is also worth to note that both HA and HS are involved in the problem of rhabdomyolysis, and whether ORSP supplementation can help solve rhabdomyolysis is also worth verifying in follow-up studies ( He et al, 2020 , 2022 ; Li et al, 2022 ). It has been reported that a kind of probiotic Akkermansia muciniphila could improve heat stress-impaired intestinal barrier function by modulating HSP27, which suggests that it is important to study the relationship between probiotics and HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between the heat shock response, intestinal barrier function, and gut microbiota nevertheless merits further investigation—particularly in terms of HA and HS. It is also worth to note that both HA and HS are involved in the problem of rhabdomyolysis, and whether ORSP supplementation can help solve rhabdomyolysis is also worth verifying in follow-up studies ( He et al, 2020 , 2022 ; Li et al, 2022 ). It has been reported that a kind of probiotic Akkermansia muciniphila could improve heat stress-impaired intestinal barrier function by modulating HSP27, which suggests that it is important to study the relationship between probiotics and HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…5 The three main components of the ECM are fibrin, glycoproteins and proteoglycans, which regulate the biochemical and mechanical properties, provide sufficient cell-ECM interactions and mediate cell-cell interactions. 6,7 Therefore, the key to achieving biomimetic cell culture is to recapitulate the ECM in vitro to provide a simulated growth environment for cells as in vivo. 8 In general, the cellular microenvironment in vivo can be approximately divided into three aspects, i.e., the spatial microenvironment, chemical microenvironment, and physical microenvironment (Fig.…”
Section: The Principle Of Biomimetic Cell Culturementioning
confidence: 99%
“…However, the relationship between the heat shock response, intestinal barrier function, and gut microbiota nevertheless merits further investigation-particularly in terms of HA and HS. It is also worth to note that both HA and HS are involved in the problem of rhabdomyolysis, and whether ORSP supplementation can help solve rhabdomyolysis is also worth verifying in follow-up studies (He et al, 2020(He et al, , 2022Li et al, 2022). It has been reported that a kind of probiotic Akkermansia muciniphila could improve heat stressimpaired intestinal barrier function by modulating HSP27, which suggests that it is important to study the relationship between probiotics and HSPs.…”
Section: Discussionmentioning
confidence: 99%